The Literature Review of Principal’s Supervision in Increasing Teacher’s Competence and Performance - Herlina, Herlina (PPSDP International Journal of Education, 2023)
This study was to review the literature on the principal’s function as a supervisor to raise teacher performance and competency. The study involved looking at 15 papers with the keyword “supervising school principals” in the title. The goal of the systematic literature review (SLR) method employed in this study is to locate, evaluate critically, and incorporate prior research on the function of the principal as a supervisor in enhancing teacher performance and competence. The findings of this literature review research allow us to draw the conclusion that the supervision process is one factor that is quite important in evaluating the efficacy of current management in schools. There is a positive and significant relationship between the principal’s successful supervision and the effectiveness and competence of teachers. The implementation of teachers’ primary responsibilities can be improved through improved communication between teachers and school principals as well as through conducting training and training. A school principal’s roles include those of educator, manager, administrator, supervisor, leader, innovator, entrepreneur, and motivator.